Mathematics : a minimal introduction - Buium, Alexandru (CRC Press, 2014)
"Minimizing the role of intuition, this text provides an introduction to pure mathematics for a one-semester undergraduate-level course. It builds on topics in algebra, geometry, and calculus from scratch in a non-circular way using many examples and exercises. Remarks scattered throughout the text address various philosophical and historical issues, putting the mathematics into context. The author uses easy-to-follow language and avoids overwhelming students with unnecessary material"--